2022
DOI: 10.1016/j.cell.2021.12.046
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Omicron-B.1.1.529 leads to widespread escape from neutralizing antibody responses

Abstract: On the 24 th November 2021 the sequence of a new SARS CoV-2 viral isolate Omicron-B.1.1.529 was announced, containing far more mutations in Spike (S) than previously reported variants. Neutralization titres of Omicron by sera from vaccinees and convalescent subjects infected with early pandemic as well as Alpha, Beta, Gamma, Delta are substantially reduced or fail to neutralize. Titres against Omicron are boosted by third vaccine doses and are high in cases both vaccinated and infected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

74
836
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 896 publications
(946 citation statements)
references
References 67 publications
74
836
1
3
Order By: Relevance
“…5a). The IgG endpoint GMTs reached ~2.1×10 4 (20 µg), ~1.6×10 4 (100 µg dose) and ~7×10 3 (500 µg dose) for circRNA RBD vaccines, while circRNA Ctrl or PBS-immunized rhesus macaques failed to induce RBD-specific antibodies (Fig. 5b).…”
Section: Circrna Vaccine Elicited Potent Neutralizing Antibodies and Th1-biased Immune Responses In Rhesus Macaquesmentioning
confidence: 97%
See 2 more Smart Citations
“…5a). The IgG endpoint GMTs reached ~2.1×10 4 (20 µg), ~1.6×10 4 (100 µg dose) and ~7×10 3 (500 µg dose) for circRNA RBD vaccines, while circRNA Ctrl or PBS-immunized rhesus macaques failed to induce RBD-specific antibodies (Fig. 5b).…”
Section: Circrna Vaccine Elicited Potent Neutralizing Antibodies and Th1-biased Immune Responses In Rhesus Macaquesmentioning
confidence: 97%
“…The circRNA RBD-Omicron vaccine could induce Omicron Spike-specific antibodies with the endpoint GMTs of ~4.7×10 4 for 5 µg dose and ~2.2×10 5 for 10 µg dose (Fig. 4d), yielding evident neutralizing activities against Omicron with the NT50 of ~2.5×10 3 for the 5 µg dose and ~8.6×10 3 for the 10 µg dose (Fig. 4e).…”
Section: Circrna Rbd-omicron Vaccine Elicited Neutralizing Antibodies Against Omicronmentioning
confidence: 99%
See 1 more Smart Citation
“…This variant was detected on 6 continents within a month of its initial discovery and has raised concerns around the world. The omicron VOC is a heavily mutated SARS-CoV-2, with 30 amino acid substitutions, deletion of six residues, and insertion of three residues in the spike protein, mostly concentrated around the receptor binding motif (88). Among the mutations, an insertion (ins214EPE) in spike that was not been previously observed in other SARS-CoV-2 variants (140).…”
Section: Emerging Sars-cov-2 Variants Of Concernmentioning
confidence: 99%
“…These findings suggest that the omicron variant may be associated with lower COVID-19 vaccine effectiveness. Regarding the effect of neutralizing activity against monoclonal antibody-based therapies, recent findings showed that the omicron VOC substantially reduces neutralization by most of a large panel of potent monoclonal antibodies and antibodies under commercial development (88). The impact of omicron on disease severity, death and hospitalization is yet to be answered.…”
Section: Emerging Sars-cov-2 Variants Of Concernmentioning
confidence: 99%